A PHILOSOPHICAL-ETHICAL ANALYSIS OF THE FORMATION OF ADOLESCENT LIFE GOALS UNDER THE INFLUENCE OF SOCIAL MEDIA ALGORITHMS (Eureka Journal of Humanities and Social Research, 2026)
This article examines, from a philosophical-ethical standpoint, the influence exerted by social media algorithms on the formation of adolescent identity and moral autonomy. Drawing on a critical analysis of international and Uzbek scholarship published between 2020 and 2025, the study clarifies how algorithmic curation impacts the theory of autonomy advanced by J. Raz, and explicates the philosophical-ethical consequences of the phenomena commonly described as the “information bubble” and the “echo chamber.” The article conceptualizes algorithmic foreclosure as a new identity status and discusses how it can be used to extend the classical four-stage paradigm of identity advanced by J. Marcia.
Keywords: Algorithmic identity, moral autonomy, information bubble, digital ethics, adolescent identity, algorithmic foreclosure, philosophical anthropology, digital literacy, “Tuzuk-i Timuri.”